Exploring the Differences of Managers' Mental Model - Ozen, Umit; Ulengin, Fusun (Informa UK Limited, 2004)
SUMMARY The aim of this research is to propose a framework that will guide the corporations in their policy making and strategic planning activities. The proposed tool will help the group members to articulate their business vision and the comprehensive set of strategic objectives which will result in a clear understanding of the strategic direction of the corporation. It will also be possible to satisfy agreement on strategies, good cooperation, teamwork, with an effective communication among group members. Finally, it will also be possible to underline the basic similarities and differences of opinions among the members of a management team and to see whether there are subgroups which have dominant roles in the structure of a shared map.